Pengaruh Jenis Bahasa Narasi dan Bentuk Pesan Visual Video Terhadap Peningkatan Pengetahuan tentang Penyakit Chikungunya pada Siswa SMAN 1 Ciampea - M. Alif; S.H. Nasution; F. Rohadji (Jurnal Komunikasi Pembangunan, 2008)
This research was conducted to determine the influences of the type of naration language and video visual messagetoward the improvement of knowledge on Chikungunya, among students of SMAN 1 Ciampea, Bogor. Thisexperiment had been conducted to 80 students which were selected purposively and divided into four treatmentgroup. Data was analyzed using paired sample t-test, analysis of varians, and Duncan’s multiple range test. Theresult shows that, there is an improvement of knowledge, among students after watching the video on Chikungunya.However, there is no significant difference of knowledge on Chikungunya, on the influence of the use of Sundaneseand Bahasa Indonesia. Similarly, there is no significant difference about the video treatment between realisticvisualization (motion) and graphic visualization (still). All four treatment combinations do not show any significantdifference in the student’s knowledge improvement on Chikungunya.